Analisis faktor yang berhubungan dengan kejadian infeksi menular seksual melalui prostitusi online di Kota Kendari Tahun 2024 - Gamasatri, Andi Ermira Nanda; Sabilu, Yusuf; Lestari, Hariati (PT WIM Solusi Prima, 2024)
Introduction: Online prostitution is the practice of prostitution using the internet network or social media as a means of liaison or communication for pimps, sex workers and their users. In the context of online prostitution, the incidence of sexually transmitted infections (STIs) is a public health problem because it can increase the risk of contracting sexually transmitted infections (STIs). This research aims to determine knowledge factors, environmental factors and attitude factors related to the incidence of sexually transmitted infections through online prostitution in West Kendari District, Kendari City. Methods: The sampling technique used was total sampling. The population in this study was 59 people recorded at the Southeast Sulawesi Regional Police with a total sample of 59 people. Results: The research results show that knowledge has no relationship with the p significance value, namely 0.826, the environment has a relationship with the p significance value, namely 0.032, attitude has a relationship with the p value, namely 0.015. Conclusions: Based on the results of this research, it is hoped that there will be an increase in respondents' awareness of taking steps to prevent STIs, namely using safety precautions consistently and always checking their health conditions and carrying out treatment if they are indicated to be suffering from an STI. Pendahuluan: Prostitusi online adalah penggunaan internet dan jejaring sosial sebagai sarana kontak dan komunikasi antara mucikari, pekerja seks, dan kliennya. Prevalensi Infeksi Menular Seksual (IMS) dalam konteks prostitusi online menjadi perhatian kesehatan masyarakat karena meningkatkan risiko tertular IMS. Penelitian ini bertujuan untuk mengetahui faktor pengetahuan, faktor lingkungan dan faktor sikap berhubungan dengan kejadian infeksi menular seksual melalui prostitusi online di Kecamatan Kendari Barat Kota Kendari. Metode: Teknik pengambilan sampel yang digunakan adalah total sampling. Jumlah populasi dalam penelitian ini sebanyak 59 orang yang terdata di Polda Sulawesi Tenggara dengan total sampel yaitu 59 orang. Hasil: Hasil Penelitian menunjukan bahwa pengetahuan tidak memiliki hubungan dengan nilai signifikasi p yaitu 0.826, lingkungan memiliki hubungan dengan nilai signifikasi p yaitu 0.032, sikap memiliki hubungan dengan nilai p yaitu 0.015. Kesimpulan: Berdasarkan hasil penelitian ini, diharapkan adanya peningkatan kesadaran responden untuk melakukan tindakan pencegahan IMS, yaitu penggunaan pengaman dengan cara konsisten dan senantiasa memeriksakan kondisi kesehatan serta melakukan pengobatan jika terindikasi menderita IMS.